An easily accessible aggregation-induced emission probe for lipid droplet-specific imaging and movement tracking. Issue 5 (23rd December 2016) - Gao, Meng; Su, Huifang; Li, Shiwu; Lin, Yuhan; Ling, Xia; Qin, Anjun; Tang, Ben Zhong
Abstract : An easily accessible aggregation-induced emission (AIE) probe is developed for LD-specific imaging and dynamic movement tracking with advantages of NIR two-photon excited red emission and fast cell permeability. Abstract : Lipid droplets (LDs) as dynamic organelles are associated with many metabolic processes. Ideal fluorescent probes for LD-specific imaging require excellent specificity, superior brightness, fast cell permeability, and easy preparation. However, conventional fluorophores for LD imaging suffer from drawbacks of aggregation-caused quenching (ACQ), poor photostability, and difficulty of preparation. To tackle these challenges, herein, we develop an easily accessible aggregation-induced emission (AIE) fluorescent probe for LD-specific imaging and dynamic movement tracking. This AIE probe has significant advantages in terms of fast cell permeability, low cytotoxicity, strong photostability, and high two-photon absorption cross-sections in the near infra-red (NIR) range. It is thus expected to have broad applications in the study of LDs' biological functions.